El Niño drought increased canopy turnover in Amazon forests. Issue 3 (25th March 2018) - Leitold, Veronika; Morton, Douglas C.; Longo, Marcos; dos‐Santos, Maiza Nara; Keller, Michael; Scaranello, Marcos
Summary: Amazon droughts, including the 2015–2016 El Niño, may reduce forest net primary productivity and increase canopy tree mortality, thereby altering both the short‐ and the long‐term net forest carbon balance. Given the broad extent of drought impacts, inventory plots or eddy flux towers may not capture regional variability in forest response to drought. We used multi‐temporal airborne Lidar data and field measurements of coarse woody debris to estimate patterns of canopy turnover and associated carbon losses in intact and fragmented forests in the central Brazilian Amazon between 2013–2014 and 2014–2016. Average annualized canopy turnover rates increased by 65% during the drought period in both intact and fragmented forests. The average size and height of turnover events was similar for both time intervals, in contrast to expectations that the 2015–2016 El Niño drought would disproportionally affect large trees. Lidar–biomass relationships between canopy turnover and field measurements of coarse woody debris were modest ( R 2  ≈ 0.3), given similar coarse woody debris production and Lidar‐derived changes in canopy volume from single tree and multiple branch fall events. Our findings suggest that El Niño conditions accelerated canopy turnover in central Amazon forests, increasing coarse woody debris production by 62% to 1.22 Mg C ha −1  yr −1 in drought years .